Pharmacognostic Study of Donkey Ear Taro Leaves (Alocasia polly) - Surahmaida, Surahmaida; Aisa, Iis (Jurnal Biologi Tropis, 2025)
The donkey ear taro plant (Alocasia polly) is an ornamental Araceae family plant with broad leaves capable of absorbing air pollutants. This research examined the macroscopic and microscopic characteristics of A. polly leaves for botanical identification and pharmaceutical potential assessment. The research methods included sample preparation and macroscopic, organoleptic, and microscopic observations of fresh leaves and leaf powder. Macroscopic observations revealed shield-shaped leaves (peltatus) with pointed tips (acuminatus), ear-like lobed base (auriculatus), smooth glossy surface (nitidus), dark green upper surface, purplish lower surface, pinnate venation (penninervis), and wavy margins (repandus). The leaves averaged 33 cm in length and 16.5 cm in width. Organoleptic examination showed fresh leaves with dark green upper surfaces and purplish-brown lower surfaces, characteristic leaf aroma, and tasteless properties. The leaf powder exhibited similar dark green coloration, characteristic aroma, and tasteless qualities. Microscopic analysis of both fresh leaves and powder revealed epidermal cell structures, spiral-type vascular bundles, anomocytic stomata, multicellular and unicellular trichomes, and calcium oxalate crystals. These findings provide fundamental botanical identification data for A. polly leaves. Further research is recommended, including non-specific parameter testing and phytochemical screening, to explore the plant's pharmacological potential more comprehensively.